Design of a Crowdlending System for Formalized SMEs Based on Smart Contracts in Metropolitan Lima - Tornero-Cortés, Fabriccio (2023)
In Metropolitan Lima, small and medium-sized enterprises (SMEs) face significant challenges in obtaining financing, primarily due to high interest rates and stringent requirements from traditional financial institutions. This research introduces a crowdlending system based on smart contracts backed by blockchain technology as a solution to these obstacles. A validation with end users was conducted, and the results obtained demonstrated an impressive compliance rate of 99%. This innovative approach provides a secure, transparent, and efficient environment, offering a robust solution to the financing needs of SMEs in the region.